Improved heuristics for finite word-length polynomial datapath optimization - Alizadeh, B.; Fujita, M. (2009 IEEE/ACM International Conference on Computer-Aided Design - Digest of Technical Papers, 2009)
Conventional high-level synthesis techniques are not able to manipulate polynomial expressions efficiently due to the lack of suitable optimization techniques for redundancy elimination over Z 2 n . This paper, in comparison with, presents 1) an improved partitioning heuristic based on single-variable monomials instead of checking all sub-polynomials, 2) an improved compensation heuristic which is able to compensate monomials as well as coefficients, and 3) a combined area-delay-optimized factorization approach to extract the most frequently used sub-expressions from multi-output polynomials over Z 2 n . Experimental results have shown an average saving of 32% and 27.2% in the number of logic gates and critical path delay respectively compared to the state-of-the-art techniques. Regarding the comparison with, the number of gates and delay are improved by 14.3% and 13.9% respectively. Furthermore, the results show that the combined area-delay optimization can reduce the average delay by 26.4%.